Philosophy of education - Hermosa, Jherwin P.; Callo, Eden C.; Andal, Edilberto Z. (Quezon City : Central Book Supply, Inc., 2023)
"In a nutshell, we can define education as facilitating learning or acquiring knowledge, skills, values, beliefs and habits. This book, Philosophy of Education, aims to help readers recognize the worth of the philosophy of education and examine their role and significance in the whole process of education, particularly in the Philippines."
Includes glossary and bibliography.
English.
Keywords: Philosophy; Education